Instituto de Biología Agrícola de Mendoza (IBAM). The tenth birthday of a research envision with international impact but strongly involved with the territory - Bottini, Rubén (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2019)
At the beginning of the 2000’ a small group of researchers belonging to the Facultad de Ciencias Agrarias (FCA), began meeting regularly with colleagues from other institutions in a sort of "scientific club" then called Centro de Biología Vegetal de endoza (CEBIVEM). The aim of this group was to carry on seminars to discuss the advances either of the CEBIVEM members and/or the state of arts in some specific subjects related to plant biology and associated organisms. From the beginning, the holistic vision of plants and their environment was clear.